Analysis of glycoproteins in serum of type 2 diabetes mellitus patients - Minh Phuong, Nguyen Thi; Thanh, Tran The; Nhi, Nguyen Bich; Chi, Phan Van (Academia Journal of Biology, 2014)
Type 2 diabetes mellitus is a metabolic disorder that is primarily characterized by insulin resistance. This disease is not infectious but common in the world. Type 2 diabetes mellitus may lead to many dangerous complications such as diabetic retinopathy, possible blindness, risk of heart stroke, diabetic neuropathy, chronic diarrhea, kidney failure... Recently, many investigations have been carried out to search for effective therapies which can then be used to diagnose and cure this disease. However, most of known therapies are mainly based on measurement of blood glucose levels, which does not allow detecting the early stage of diabetes disease. To overcome this disadvantage, biomarkers, that are very promising factor to early prognosis of type 2 diabetes mellitus, have recently been considered and searched. In this study, such biomarkers were looked for by employing proteomics tools. Lectin concanavalin A (ConA) was used to receive glycoproteins from human serum. These collected glycoproteins were then digested and analyzed by nanoLC coupled with ESI MS/MS. Afterward, 57 glycoproteins were identified. In addition, glycoprotein expression level of the patients was compared with that of healthy individuals by using 2-D electrophoresis technique. As a result, expression of five proteins (haptoglobin alpha 2 chain, alpha-2-HS-glycoprotein, clusterin percursor, Apolipoprotein E percursor, Anti TNFa antibody light chain) increased significantly.